Enhancement of Copper Sorption through Acid Blue 29 Treated Oil Palm Pressed Fibres - Low, K. S.; Lee, C. K.; Tan, C. L. (Universiti Putra Malaysia Press, 1996)
The removal of cupric ions from aqueous solution by natural and dyecoated palm pressed fibres was studied. Sorption was both pH and concentration dependent. The equilibrium data followed the Langmuir isotherm model with maximum copper sorption capacities of 2.41 and 7.71 mg/g for natural and dye-treated fibres respectively. The presence of other metal ions inhibited copper uptake in the following order Pb> Zn > Ni. The suppressing effects of chelators correspond to their log K values. Column studies showed that bed-depth had a more pronounced effect on copper sorption than flow rate.